KEKERASAN, KONDISI KELUARGA, DAN KESEJAHTERAAN KELUARGA PADA ANAK KORBAN KEKERASAN - Puspitawati, Herien; Djamaludin, Moh. Djemdjem; Nursanti, Husni (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
The study aimed to examine the relationship between child abuse, children’s psychological condition, the behavior, and satisfaction to family well-being. Participants were purposively selected, involved 35 children from 56 child victims of child abuse period 2007-2009 based on data from Bogor Police Station. Data collected by interview with questionnaire. Data was analyzed by descriptive and Spearman’s correlation analysis. Results showed that the variables related to child abuse include father’s education (r=-0,515;p<0,01), father's employment status (r=-0,479;p<0,01), family size (r=-0,347;p<0,05), parent and child relationship (r=-0,422;p<0,05), and social support (r=-0,450;p<0,01). In addition, there was negative correlation between sexual abuse and psychological condition and children’s behavior (r=-0,383;p<0,05), and the satisfaction of family well-being (r=-0,354; p<0,05). Spearman’s correlation also showed that there was positive relationship between social and psychological abused toward child (r=0,679, p<0,01). Positive relationships also found between satisfaction of the family well-being and the psychological condition and child behavior (r=0,428, p<0,05).